Meningkatkan Kemampuan Operasi Pengurangan Bilangan Deret Ke Bawah Dengan Meminjam Melalui Media Video Tutorial Di SDN 19 Air Tawar Barat - Zara, Zemi Virda (RC-INSTITUT, 2019)
This problem is motivated by the problems found in class IV SDN 19, West freshwater which experienced problems in carrying out a series of downward reduction operations by borrowing. The purpose of this study is to improve the ability to reduce the series down by borrowing. This study also uses the Single Subject Research approach to A-B design and data analysis techniques also use graphical visual analysis. In this study the subjects taken were students who had difficulty learning class IV SDN 19 Air Tawar Barat. The research observations were carried out in two sessions, the first session was the baseline session (A) which was held four times in different days. Then proceed with the second session, the Intervention session (B), which was held six times on different days. So that the results obtained that by using the video tutorial media can improve the ability of children to work on the problem of reducing the series of downward operations by borrowing from students with learning difficulties.